2014
DOI: 10.1021/jp500580g
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Raman Microscopy and Atomic Force Microscopy on Heterogeneous Graphene Obtained after Reduction of Graphene Oxide

Abstract: 2 graphene, graphene oxide, Raman spectroscopy, statistic Graphene oxide can be used as a precursor to graphene but the quality of graphene flakes is highly heterogeneous. Scanning-Raman-Microscopy (SRM) is used to characterize films of graphene derived from flakes of graphene oxide with an almost intact carbon framework (ai-GO). The defect density of these flakes is visualized in detail by analyzing the intensity and fullwidth at half-maximum of the most pronounced Raman peaks. In addition, we superimpose the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
104
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 41 publications
5
104
0
2
Order By: Relevance
“…Thus, it can be concluded that the quality of reduced oxo-G 1 is at least as high as the most potent chemical reduction method. 42,50,54 Characterization of the products by XPS XPS is a standard technique to determine the reduction degree of GO. High resolution C 1s spectra (see Fig S3 †) reveal a high efficiency of the reduction method.…”
Section: Characterization Of the Products By Raman Spectroscopymentioning
confidence: 99%
“…Thus, it can be concluded that the quality of reduced oxo-G 1 is at least as high as the most potent chemical reduction method. 42,50,54 Characterization of the products by XPS XPS is a standard technique to determine the reduction degree of GO. High resolution C 1s spectra (see Fig S3 †) reveal a high efficiency of the reduction method.…”
Section: Characterization Of the Products By Raman Spectroscopymentioning
confidence: 99%
“…S1 †). [41][42][43][44] Fig. 1b presents an AFM image of the oxo-G 1 lm deposited on a SiO 2 /Si substrate.…”
Section: 39mentioning
confidence: 99%
“…Chemical reduction of GO with a mixture of hydroiodic acid (HI) and trifluoroacetic acid (TFA) yields graphene with an average defect density of 0.3% (as determined by scanning Raman microscopy). 17,19 The analysis of GO reveals flakes of graphene of mono-layer in average and the mean flake size is about 5 lm. 19 This type of functionalized graphene can be symbolized according to the recent systematic study as 5lm,0.3% 8% .…”
mentioning
confidence: 99%
“…17,19 The analysis of GO reveals flakes of graphene of mono-layer in average and the mean flake size is about 5 lm. 19 This type of functionalized graphene can be symbolized according to the recent systematic study as 5lm,0.3% 8% . 20,21 For clearance, the abbreviation GO is used for this functionalized graphene throughout the manuscript.…”
mentioning
confidence: 99%
See 1 more Smart Citation